Flow Characteristics and Structure Optimization of a Baffle Plate Heat Exchanger - Lu, Mengshi; Feng, Zhuoheng; Wang, Yungang; Yang, Hongwei; Xia, Wenqing; Zhu, Haimiao; Hua, Dan (Frontiers in Energy Research, 2022)
In this paper, a theoretical model of hot and cold fluid flow, heat transfer and thermal stress coupling in baffle plate heat exchanger is established, and numerical simulation is carried out. The flow field in heat exchanger and the deformation of the heat exchange tube bundles in the baffle plate heat exchanger are studied. The optimization effect of diversion grid on the flow field at the inlet of variable section is emphasized. The influence of grid arrangement on the flow field and the performance of the tube bundles are analyzed and discussed. The results show that the backflow situation can be effectively improved and the vortex intensity in the straight section of the cold fluid inlet can be greatly reduced by adding grid. The deformation of the heat exchange tube bundles illustrates the maximum deformation with 1.39mm at the position of the strongest backflow. The deformation can be reduced by 26% due to the arrangement of diversion grid, which is helpful to improve the safety of the device.